2014
DOI: 10.1111/jawr.12248
|View full text |Cite
|
Sign up to set email alerts
|

Describing Damage to Stream Modification Projects in Constrained Settings

Abstract: Complex relationships between stream functions and processes make evaluation of stream modification projects difficult. Informed by vague objectives and minimal monitoring data, post-construction project evaluations can often be a subjective attribution of success or failure. This article provides a simple framework to rapidly describe the degree of damage in stream modification projects performed in constrained settings. Based on widely accepted evaluations of physical habitat quality and stream stability, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…channelization or damming), aimed at flood control, navigation improvement, expansion of agriculture or hydropower production, have altered the functioning of European large rivers (Brookes, 1988;Petts et al, 1989;Kondolf and Larson, 1995), including aquatic and riparian habitats and biodiversity (Bravard et al, 1986;Amoros and Petts, 1993;Dynesius and Nilsson, 1994). In order to balance these impacts by recovering fluvial processes (Knighton, 1984;Bravard et al, 1986;Naiman et al, 1993Naiman et al, , 1988Corenblit et al, 2007;Hering et al, 2015) and ecosystem services (Loomis et al, 2000;Acuña et al, 2013;Large and D. Eschbach et al: Long-term temporal trajectories of large rivers Gilvear, 2015), an increasing number of restoration projects have been carried out over recent decades (Kondolf and Micheli, 1995;Wohl et al, 2005). In Europe, this trend has been supported by the Water Framework Directive (IKSR-CIPR-ICBR, 2005;WFD, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…channelization or damming), aimed at flood control, navigation improvement, expansion of agriculture or hydropower production, have altered the functioning of European large rivers (Brookes, 1988;Petts et al, 1989;Kondolf and Larson, 1995), including aquatic and riparian habitats and biodiversity (Bravard et al, 1986;Amoros and Petts, 1993;Dynesius and Nilsson, 1994). In order to balance these impacts by recovering fluvial processes (Knighton, 1984;Bravard et al, 1986;Naiman et al, 1993Naiman et al, , 1988Corenblit et al, 2007;Hering et al, 2015) and ecosystem services (Loomis et al, 2000;Acuña et al, 2013;Large and D. Eschbach et al: Long-term temporal trajectories of large rivers Gilvear, 2015), an increasing number of restoration projects have been carried out over recent decades (Kondolf and Micheli, 1995;Wohl et al, 2005). In Europe, this trend has been supported by the Water Framework Directive (IKSR-CIPR-ICBR, 2005;WFD, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, this trend has been supported by the Water Framework Directive (IKSR-CIPR-ICBR, 2005;WFD, 2000). Restoration activities progressively target hydromorphological processes and functioning rather than "static" fluvial forms (Jenkinson et al, 2006;Beechie et al, 2010;Arnaud et al, 2015;Jones and Johnson, 2015). Numerous studies have shown that current river functioning results from complex long-term trajectories driven by natural and anthropogenic factors at different spatio-temporal scales (e.g.…”
Section: Introductionmentioning
confidence: 99%